2011
DOI: 10.3138/infor.49.4.254
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Clustering Surgical Cases to Allow Master Surgical Scheduling

Abstract: Master surgical scheduling can improve manageability and efficiency of operating room departments. This approach cyclically executes a master surgical schedule of surgery types.These surgery types need to be constructed with low variability to be efficient. Each surgery type is scheduled based upon its frequency per cycle. Surgery types that cannot be scheduled repetitively are put together in so-called dummy surgeries. Narrow defined surgery types, with low variability, lead to a large volume of such dummy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…All those surgical cases that cannot be performed are put into the so-called dummy surgeries. van Oostrum et al [60] applied a hierarchical clustering approach to real data (i.e., surgery duration and LOS) of the Beatrix Hospital (the Netherlands) allowing a volume reduction of dummy surgeries, that is the optimization of the OR utilization and a leveling of ward occupancy.…”
Section: Tactical Levelmentioning
confidence: 99%
“…All those surgical cases that cannot be performed are put into the so-called dummy surgeries. van Oostrum et al [60] applied a hierarchical clustering approach to real data (i.e., surgery duration and LOS) of the Beatrix Hospital (the Netherlands) allowing a volume reduction of dummy surgeries, that is the optimization of the OR utilization and a leveling of ward occupancy.…”
Section: Tactical Levelmentioning
confidence: 99%
“…The tactical planning is a multi-layered decision making problem starting with the identification of patient groups that need to be allocated the OR time. This study assumed that the patients' classes have already been identified but efficient methods such as cluster analyses have been identified to improve the execution of the surgery decisions (Van Oostrum et al, 2011, Dilts et al, 1995.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…This relationship is described in more detail by Schonmeyr et al [225] using queuing theory. 191,192,194,197,200,201,202,203,205,209,211,212,214,215,216,217,218,224,226,227,228,235,236,237,239,241,247,248,249,251,258,259,261,264,268,269,271,272,276,277,279,280,281,282] Integrated OR [1,2,7,10,11,12,<...>…”
Section: Supporting Facilitiesmentioning
confidence: 99%
“…In many articles a problem is defined that is specific to one single hospital and it is unclear 63, 64, 65, 67, 69, 70, 71, 72, 74, 77, 78, 81, 83, 85, 93, 94, 95, 96, 97, 98, 100, 101, 103, 104, 107, 108, 111, 113, 114, 115, 116, 122, 123, 124, 125, 129, 130, 132, 136, 138, 139, 140, 143, 144, 146, 153, 156, 159, 160, 161, 162, 168, 169, 171, 173, 174, 175, 176, 177, 181, 182, 184, 185, 187, 188, 189, 190,192,194,195,197,198,200,201,202,203,204,205,206,209,211,213,216,217,222,223,225,226,227,228,235,238,240,241,242,245,246,247,248,249,251,252,253,254,258,259,260,261,263,264,…”
Section: Testing Phasementioning
confidence: 99%